Managing psoriasis consultations during the COVID-19 pandemic: recommendations from the psoriasis group of the Spanish Academy of Dermatology and Venereology (AEDV) (2020)
Infection by the coronavirus SARS-CoV-2 and the associated disease, COVID-19, constitute a serious public health problem. Considerable uncertainty surrounds the way in which this problem will affect inflammatory diseases such as psoriasis and, in particular, patients treated with selective immunomodulators and immunosuppressants. Based on the scarce scientific evidence available and consistent with the position of other national and international scientific societies (European Academy of Dermatology and Venereology-Skin Inflammation and Psoriasis International Network, International Psoriasis Council, American Academy of Dermatology), 1–3 the Psoriasis Group of the Spanish Academy of Dermatology and Venereology (AEDV) issued a statement through the AEDV (GPs-COVID-19)4 with the aim of guiding dermatologists who treat Journal Pre-proof psoriasis, especially in cases where patients are receiving treatment or are about to initiate treatment with selective immunomodulators or immunosuppressants.